Situation Report: Hungary, 11 January 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Negative Aspects of the Five-Day Workweek as Seen by Beszelo / by Judith Pataki Hungary Finally Commissions Its First Nuclear Reactor / by Cam Hudson Ten Years of Local Border Trade / by Laszlo Rasko Hungarian Seek US Agricultural Technology / by Laszlo Rasko Lord Grant Me a Good Death / by Gabor Hajnal